IMPLIKASI PANDANGAN FILSAFAT PRAGMATISME RICHARD RORTY TENTANG EPISTEMOLOGI DALAM BIDANG PENDIDIKAN - Dardiri, Achmad (Jurnal Cakrawala Pendidikan, 2007)
truth, asare _""""..LAVJL...a.__onaA...lY...l..A.1lJ1iw'.I..by means of a i-/..l..l...lVl.Jl'Vi-/Jl.l..l"""II.4.l J1.JL'..... JLJA.JLJA._JA.J1.__.... JA....,The indicate that the views held RichardRorty's pragmatic philosophy on epistemology (about knowledgeand truth) are as follows. (1) According to Rorty, knowledge is notto be seen as a matter obtaining true reality or of reflecting naturebut acts in course of masteringa matter of dialogues. Truth is not to be interpreted asconformity between statement and reality (its correspondence tois it to interpreted as conformity between(its correspondence to thought); rather, it is to beas whenever something is good for us, webelieve in it. In this case, Rorty assumes the view of the relativity oftruth. According to him, if we wish to find justification of truth, weshould seek it society by conducting dialogues, which are to bereferred to as social justification or dialogical justification.